Clinical features and outcomes of spinal cord infarction following vertebral artery dissection: a systematic review of the literature. (September 2013) - Hsu, Chia-Yu; Cheng, Chun-Yu; Lee, Jiann-Der; Lee, Meng; Huang, Ying-Chih; Wu, Chih-Ying; Hsu, Huan-Lin; Lin, Ya-Hui; Huang, Yen-Chu; Weng, Hsu-Huei; Huang, Kuo-Lun
Abstract : Objective: Spinal cord infarction (SCI) is a rare complication of vertebral artery dissection (VAD). Its clinical features and outcomes have not yet been well documented. Methods: In addition to reporting a case with bilateral SCI caused by left VAD, we performed a systematic review of the literature conducted through a PubMed search. Results: A total of 17 cases were reviewed (nine men and eight women). The average age was 40·5±14·6 years. In addition to neck pain or headache (88%), patients with VAD-associated SCI often presented with a sensory level (76%) or Brown–Séquard syndrome (53%). The most common regions of dissection were at the V1 or proximal V2 segments, and the infarcted area of SCI was mainly located at C2–C5 levels. Regarding the vascular territory, posterior spinal artery infarction was noted in 29% of patients, spinal sulcal artery infarction in 42%, and anterior spinal artery (ASA) watershed infarction in 29%. Eleven patients (65%) had a good outcome and six patients (35%) had a poor outcome (including one mortality; 6%). Smoking, age above 50 years, and ASA watershed infarction were associated with a poor outcome, while spinal sulcal artery infarction was associated with a good outcome. Conclusion: Neck pain or headache is an important warning symptom of VAD, and the presence of a concomitant sensory level or Brown–Séquard syndrome is helpful for the early diagnosis of SCI caused by VAD. One-third of patients had a poor outcome, and smoking, old age, and ASA watershed infarction represented important risk factors.